Protocolo MAC anycast com preâmbulos avançados para redes de sensores sem fio - Araújo, Gustavo Figueiredo (2017)
Wireless sensor networks use duty-cycling to save energy, with the cost of increasing latency in message routing due to additional hops. Cross-layer protocols that use anycast communication achieve a latency reduction in asynchronous WSNs that operate in duty-cycles. A series of preambles is sent in order to find the next hop, which is selected from a forwarding candidate set (FCS). This work proposes a new cross-layer protocol named APA-MAC (Advanced Preamble Anycast for MAC layer), for the delivery of messages with low latency in wireless sensors networks that employ duty-cycling. In the APA-MAC protocol, the preambles propagate ahead, creating a propagation path to the destination, and the data message follows this path few hops behind. The data transmission to the next hop is triggered by a signal indicating the vacancy of the channel. Due to this mechanism, transmissions of preambles do not have to be interrupted if the data message approaches the area. Therefore, the simultaneous propagation of preambles and data message, with the uninterrupted transmission of preambles, is responsible for latency reduction in the APA-MAC. In addition, based on the size of the data message, the cardinality of the FCS is defined in order to accelerate the propagation of the preambles, avoiding that at the time of receiving the data, the node finds the channel occupied. The results of the simulation showed that the proposed protocol maintains a low power consumption, achieving at least 10% less latency in relation to the other evaluated asynchronous MAC protocols. Moreover, the rate of successfully transmited messages is about 98% in collisions prone scenarios.